1980
DOI: 10.1136/jcp.33.11.1029
|View full text |Cite
|
Sign up to set email alerts
|

IgM associated primary diffuse mesangial proliferative glomerulonephritis.

Abstract: Twenty-three cases of IgM associated primary diffuse mesangial proliferative glomerulonephritis are presented. In 18, IgM was the sole localising host immunoglobulin, and it was the predominant globulin in five; C3 was also present in 18. Light microscopy revealed variable diffuse and global mesangial proliferation in all cases, with additional focal global sclerosis in 16, focal segmental sclerosis in 15, and small capsular crescents in seven. Material for electron microscopy was available from 19 patients; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 12 publications
5
79
1
2
Order By: Relevance
“…3 Patients with mesangial expansion or mesangial proliferation by light microscopy frequently have abundant glomerular IgM deposition. 4 Glomerular IgM is also observed in many secondary forms of glomerulosclerosis, including diabetic nephropathy 5 and hypertensive nephropathy. 6 Importantly, C3 and C4 are frequently detected in the glomeruli of patients who have IgM deposits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Patients with mesangial expansion or mesangial proliferation by light microscopy frequently have abundant glomerular IgM deposition. 4 Glomerular IgM is also observed in many secondary forms of glomerulosclerosis, including diabetic nephropathy 5 and hypertensive nephropathy. 6 Importantly, C3 and C4 are frequently detected in the glomeruli of patients who have IgM deposits.…”
mentioning
confidence: 99%
“…6 Importantly, C3 and C4 are frequently detected in the glomeruli of patients who have IgM deposits. 4,7,8 In spite of its promiscuous presence in glomerular lesions, a pathogenic role for glomerular IgM has not been demonstrated. Some series, however, have shown that the presence of IgM is of prognostic significance.…”
mentioning
confidence: 99%
“…Most of the studies have reported on prevalence of IgMN as frequency/ percentage of renal biopsies with diagnosis of IgMN reported from 2 % to 18.5 % in native biopsies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Occasional cases of IgMN in transplant biopsies have also been reported (14).…”
Section: Epidemiologymentioning
confidence: 99%
“…Glomeruli show diverse grade of mesangial hypercellularity or no changes by light microscopy [1] . However, recent edition of Heptinstall's pathology of the kidney (7 TH edition) defines IgMN as cases with bright staining (at least two positive out of three) and with demonstrable mesangial deposits on electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Two articles published in 1978 by independent groups [4,5] are considered by many authors to be the first descriptions of a glomerulopathy characterised by diffuse mesangial deposits of immunoglobulin M (IgM) in patients with relatively normal light microscopy. The disease, like IgA nephropathy (IgAN), is defined by its immunohistologic features: the presence of IgM as the sole or dominant immunoglobulin in the mesangial regions of the glomeruli in a diffuse (all glomeruli) and global (the entire glomerulus) distribution [4][5][6][7] . Its incidence varies, in accordance with different series, between 4.8% and 8.6% of all renal biopsies, affecting all ages and without predilection for gender [6,8,9,10] .…”
Section: Introductionmentioning
confidence: 99%